MODERN UNDERSTANDING OF IMMUNOLOGICAL ASPECTS OF BONE REGENERATION - Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The immune system plays an active role in the regeneration of bone tissue. This reasoning can be based on the peculiarity of populations of immune cells, which, as is known, are diverse and heterogeneous. Such functional and cytological versatility of bone tissue may indicate the similarity of their natural relationship. The basis of this connection is regenerative processes, which we decided to describe in this review scientific article. Fundamental information about the bone cell system points to the fact that the monocytic line of bone marrow stem cells is considered a matrix for the formation of macrophages. Along with this, it is this ancestral line of the cell that acts as the basis for the regeneration of the bones of the skeleton – osteoclasts.